2007
DOI: 10.4103/0255-0857.34776
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous nocardial abscess in a post-renal transplant patient

Abstract: A case of nocardiosis in a post-renal transplant patient is being reported for the Þ rst time from Eastern India. The patient had multiple abscesses on the right thigh and chest. Direct examination of the aspirated pus by Gram stain and modiÞ ed Ziehl Neelsen stain revealed gram-positive beaded, partially acid-fast, branching Þ laments. Culture of the pus yielded Nocardia asteroides. The patient responded to surgical drainage and sulphamethoxazole therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Thus, each case needs a careful multidisciplinary evaluation by the primary physician, the infectious diseases specialist, and the surgeon. Mycetoma, some ocular infections, and rare cases with other body sites involvement may require surgical treatment [37,[65][66][67][68][69].…”
Section: Treatmentmentioning
confidence: 99%
“…Thus, each case needs a careful multidisciplinary evaluation by the primary physician, the infectious diseases specialist, and the surgeon. Mycetoma, some ocular infections, and rare cases with other body sites involvement may require surgical treatment [37,[65][66][67][68][69].…”
Section: Treatmentmentioning
confidence: 99%
“…Devi et al reported the first case from eastern India of nocardiosis in a renal transplant patient presenting as subcutaneous abscess. 5 The lack of clinical data and consequent underreporting of nocardiosis is believed to be due to various factors. These include difficulty in disease diagnosis due to unfamiliarity with the disease, non-specific or lack of pathognomonic clinical presentation, presence of common and easily diagnosed co-infections that preclude further work-up for nocardiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Talaromyces marneffei is a thermally dimorphic fungus that causes the opportunistic infection, talaromycosis, mostly in immunocompromised patients such as individuals with leukemia, neutropenia, auto-interferon gamma autoantibodies, and AIDS. In fact, in T. marneffei endemic areas, infection is very common and has been recognized as a disease indicative of AIDS ( Supparatpinyo et al., 1994 ; Supparatpinyo and Sirisanthana, 1994 ; Devi et al., 2007 ). There are over an estimated 8,000 cases of life-threatening T. marneffei infections annually with mortality rates of 2-75% ( Pal, 2017 ).…”
Section: Introductionmentioning
confidence: 99%